Evaluation of the Effectiveness of Pharmaceutical Prescription Services Through the "SIANTARO" (Ready to Deliver Drugs) Program - Winarti Winarti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Pharmaceutical services are an essential component of hospital healthcare, with prescription waiting time serving as an important indicator of service quality. Long waiting times may reduce patient comfort and satisfaction and contribute to overcrowding in pharmacy service areas. This study aimed to evaluate the effectiveness of the SIANTARO (Ready to Deliver Medicine) program in improving outpatient pharmaceutical services at Nganjuk Regional General Hospital. A mixed-methods approach with an exploratory observational design was employed over three months. A total of 120 outpatients were selected using purposive sampling. Data were collected through a time-motion study, drug handover verification forms, and a Likert-scale patient satisfaction questionnaire. The results showed that SIANTARO reduced patients' physical waiting time from an average of 85 minutes to 12 minutes, representing an 85.8% improvement in time efficiency. Among respondents, 68.5% reported being very satisfied and 26.0% satisfied with the service. The program also strengthened medication distribution safety through sealed tamper-evident packaging and improved medication information services through brochures, pill boxes, and telepharmacy. The patient satisfaction index increased from 71.2% to 94.5%. SIANTARO demonstrates potential as a patient-centered innovation for improving pharmaceutical service efficiency, safety, accessibility, and satisfaction.